2006
DOI: 10.1063/1.2234281
|View full text |Cite
|
Sign up to set email alerts
|

On the existence of Einstein oscillators and thermal conductivity in bulk metallic glass

Abstract: Low-temperature specific heat and thermal conductivity of bulk metallic glasses are measured to identify the primary vibrational modes associated with their unique structures. An Einstein-type localized vibrational mode with an Einstein temperature of 112 K is found in bulk metallic glass Ni 59.5 Nb 33.6 Sn 6.9 . This localized vibrational mode causes resonant scattering of phonons and results in the localization of phonons which leaves the phonon hopping conduction the limiting mechanism of thermal transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 19 publications
0
16
1
Order By: Relevance
“…Low-energy Einstein oscillator-type vibrational modes have been observed previously in metallic systems, 39,40 however the low-temperature specific heat observed here is not consistent with a single oscillator with a welldefined frequency. On the other hand the alternative explanation of a narrow electronic pseudogap, which could produce the low-temperature reduction in specific heat as observed here, seems unlikely since an extremely narrow gap would be required.…”
Section: Discussioncontrasting
confidence: 66%
“…Low-energy Einstein oscillator-type vibrational modes have been observed previously in metallic systems, 39,40 however the low-temperature specific heat observed here is not consistent with a single oscillator with a welldefined frequency. On the other hand the alternative explanation of a narrow electronic pseudogap, which could produce the low-temperature reduction in specific heat as observed here, seems unlikely since an extremely narrow gap would be required.…”
Section: Discussioncontrasting
confidence: 66%
“…Granato suggested that interstitial defects behave as Einstein oscillators (the presence of such oscillators in MGs was repeatedly mentioned in the literature, e.g., Ref. ) and their low‐frequency vibration modes contribute to the heat capacity. The BP height is then expected to be linear in the defect concentration .…”
mentioning
confidence: 91%
“…1) Inoue et al have found that bulk metallic glassy (BMG) alloys can be obtained even by conventional casting techniques at relatively slow cooling rates, and have also reported that a number of metallic glasses can be formed by quenching in ZrCu, NiZr, PdCu alloy systems. 24) As summarized by Inoue, BMG alloys exhibit three common features as follows: (1) They mostly belong to multicomponent systems, (2) they have significant atomic size ratios of above 12%, and (3) they exhibit negative heats of mixing among the constituent elements. The satisfaction of these principles leads to a high glass transition temperature, T g and a low liquidus temperature.…”
Section: Introductionmentioning
confidence: 99%